Detection of real-time fluorescence quantitative polymerase chain reaction for colonization of Bacillus amyloliquefaciens and Trametes versicolor in Juglans sigllata Dode rhizosphere soil - Zheng Lei; Zhang Jing; Peng Yan; Ma Wenjian; Zhu Tianhui (浙江大学学报. 农业与生命科学版)
Juglans sigllata Dode, is widely planted in Liangshan Prefecture of southwest China for its nuts and wood. Liangshan Prefecture is a major traditional growing area of J. sigllata and has unique advantages for walnut industrial development because of its good soil, climate, and availability of water. Currently there are 2.7 million hectares of walnut, contributing important incomes for farmers. In April 2013, numerous J. sigllata were found to be infected with root rot in the Muli County of Liangshan Prefecture. Symptoms included dried leaves, dead branches, and even death. According to the cultural characteristics, the fungus was primarily identified as Fusarium solani and it could cause the root rot on many industrial crops. Fusarium solani could be significantly antagonized by Bacillus amyloliquefaciens and Trametes versicolor.In order to control the plant diseases caused by F. solani, B. amyloliquefaciens and T. versicolor were chosen for testing the efficiency of the colonization in rhizosphere soil of J. sigllata. With the development of real-time fluorescence quantitative polymerase chain reaction (PCR) technology, more attention was paid on this issue. It was highly efficient, sensitive and specific technology and had been widely used in various fields of scientific research. For the research of the root rot of J. sigllata, the dynamic changes of two kinds of biocontrol strains and the pathogen in rhizosphere soil were studied through the method of real-time fluorescence quantitative PCR.The results showed that biocontrol strains multiplied rapidly after inoculation, and the relative content of B. amyloliquefaciens reached the peak at the 20th day. Then, the relative content of B. amyloliquefaciens was declined, and kept stable after the 40th day. But the time when the relative content of T. versicolor showed the growth peak and stabilization at each stage was delayed for 10 d as compared with B. amyloliquefaciens. After 60 days, the relative contents of F. solani in rhizosphere soil inoculated with B. amyloliquefaciens and T. versicolor were reduced significantly when the relative content of biocontrol strains reached the peak. The difference in the content of B. amyloliquefaciens was significant between the treatment with or without inoculating B. amyloliquefaciens, while more distinctions of the content of T. versicolor between the treatment with or without inoculating T. versicolor. When the colonization was stabilized, the content of B. amyloliquefaciens had no significant difference compared with the control, while the content of T. versicolor was significant between the two treatments.All above indicate that the biocontrol efficiency and the colonization ability of B. amyloliquefaciens are superior than T. versicolor. This study can provide real-time monitoring of diseases caused by F. solani and support the detection of the colonization of B. amyloliquefaciens and T. versicolor in rhizosphere soil.